Development of Ti-doped iron-polyoxocarbosilane nanocomposite with sensing properties by single-step laser pyrolysis. (23rd August 2010) - Morjan, I.; Alexandrescu, R.; Scarisoreanu, M.; Birjega, R.; Dumitrache, F.; Gavrila, L.; Fleaca, C.; Soare, I.; Ciupina, V.; Simion, C.E.; Tomescu, A.
Nanoscale metal-polymer nanocomposites present new and often superior physical-chemical properties. In this paper, results concerning the preparation of Ti-doped Fe/Fe2O3/polyoxocarbosilane nanocomposites are reported. Nanocomposite powders with different polymer content were prepared by the single-step infrared laser pyrolysis of a gas mixture containing iron pentacarbonyl, hexamethyldisiloxane and titanium tetrachloride. The structural properties of the as-synthesised and calcined (in air, at 500°C) nanopowders were studied using different analytical techniques. In view of potential applications, sensor tests to NO2 and CO of the pure and Ti-doped thick films were also performed.